Economic Analysis of Developing a Sustainable Aviation Fuel Supply Chain Incorporating With Carbon Credits: A Case Study of the Memphis International Airport - Sharma, Bijay P; Yu, T. Edward; English, Burton C.; Boyer, Christopher N. (Frontiers in Energy Research, 2021)
Sustainable aviation fuel (SAF) has been considered as a potential means to mitigate greenhouse gas (GHG) emissions from the aviation sector, which is projected to continuously expand. This study examines the impact of developing a SAF sector along with carbon credits on carbon equivalent emissions from aviation using a Stackelberg leader-follower model that accounts for economic interaction between SAF processor and feedstock producers. The modeling framework is applied to an ex-ante optimization of commercial scale SAF production for the Memphis International Airport from the switchgrass-based alcohol-to-jet pathway. Results suggest that supplying 136 million gallons of SAF to the Memphis International Airport annually could reduce 62.5% of GHG emissions compared to conventional jet fuel (CJF). Incorporating with carbon credits, SAF could lower GHG emissions by about 65% in total from displacing CJF and generate additional welfare gains ranging between 12 and 51 million annually compared to the case without carbon credits. In addition, sensitivity analysis suggests advancing SAF conversion rate from biomass could lower the SAF break-even considerably and enhance the competitiveness of SAF over CJF.